ESTETIKA BUNYI DAN MAKNA DALAM TEKS NYANYIAN ANAK-ANAK SUKU AKIT DESA TELOK SETIMBUL KECAMATAN MERAL BARAT KABUPATEN KARIMUN - M. Hanafis '; Dudung Burhanudin; Hadi Rumadi (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: This study discusses the Aesthetics of sound and meaningin the singing children’s text Akit tribal village west bay setimbul meral district court district Karimun. The interesting thing about this study is the text object, “singing” that should be preserved due to the nature that it is rich in aesthetic elements. Problems examined through children's song texts are (1) how aesthetic sound and (2) how is the meaning in the text of the song of children. Aesthetic sound and meaning are able to deepen the meaning and describe things that are spoken through the language of the song writer in order to touch feelings. The study was categorized as a qualitative study using descriptive analysis method. The research data is in the form of a children’s song lyric taken from information of people. Data were analyzed based on the aesthetic elements that include a) rhyme, b) efoni, c) kakafoni, d) alliteration, e) assonance, f) anaphora, g) epifocal, h) onomatopoeic, and I) meaning. Based on the results of the study, the researcher found 5 data of rhyme beginning, 8 data on middle rhyme, 9 data on rhyme ending sequence, 10 data on rhyme late in pairs, 3 data on rhyme late intermittent, 3 data on the final rhyme hugged, 19 data on efoni 20 Data on kakafoni, 13 data on alliteration, 12 data on assonance, 5 data on anaphora, 8 data on epifocal, 4 data on onomatopoeic and 22 data on meaning (sentence connotation). The results of this study indicate that the essence of the aesthetic object is the ability to attract someone through beauty or ugliness. The results of this study are expected to have contributed to the development of science, particularly in researching of literary aesthetics.Key words: Aesthetic, text of children’s songs, akit tribal karimun district